Forensic genetics for monitoring the illegal trade of hammerhead sharks (Sphyrna spp.) using a multiplex PCR protocol - Martins, Thais; Lutz, Ítalo; Da Silva, Raimundo; Monteiro De Lima, Gabriel; Santana, Paula; Brígida, Nicolly Santa; Vallinoto, Marcelo; Sampaio, Iracilda; Evangelista-Gomes, Grazielle (Frontiers in Marine Science, 2025)
IntroductionAll Sphyrna species occurring along the Brazilian coast are threatened with extinction, largely due to intense harvesting to supply the shark fin and meat trade. This scenario is worsened by the high vulnerability of these species to fishing pressure, resulting from their morphological, behavioral, and physiological characteristics. The lack of effective management and enforcement enables the landing and commercialization of hammerhead sharks without morphological identification, as they are often sold headless and finless. In this context, the use of alternative approaches such as forensic genetics becomes essential for species identification.MethodsWe developed a multiplex PCR protocol using the mitochondrial markers NADH dehydrogenase subunit 2 (NADH2) and tRNA-Trp for the rapid identification of S. mokarran, S. lewini, S. tudes, S. alleni and S. media. All primers were tested in silico and experimentally validated for the target species included in this study.ResultsThe species-specific primers produced distinct band profiles: S. mokarran (1,500 bp), S. lewini (1,500 and 400 bp), S. media (3,000, 700, and 400 bp), S. tudes (400 bp), and S. alleni (400 and 300 bp). The target species showed consistent band patterns across most tested concentrations, with 100 ng/µL yielding the best performance for all species. In cross-amplification tests, the protocol also allowed for the distinction of C. limbatus from Sphyrna species.DiscussionTherefore, the developed multiplex protocol represents a viable and effective tool, and based on its reproducibility, sensitivity, validation, and specificity, we recommend its application as support for enforcement actions and to help combat the illegal trade of threatened hammerhead shark species.